(3CSeGA GdUMGHI GdQhGI hdeG dcd hGMO efge ef GdCMGOjKs - (3Ydj Hf CMeO Hf SYjO Hf MRe GdXGgQj, GHf MRe , CHh eMeO ,J (B456 (3g` s
(3ChdgG (B:s
(3PcQ ef Qhi Yf GdfHi Udi Gddg Ydjg hSde ef GdUMGHI QVhGf Gddg Ydjge s
(3BNQgG (B:s
(3Ce YGeQ Qajbg MHjHg HfJ CHj JLQGI HfJ MeRI GHf YHO GdeWdH GNQg hGddg GYde s
(3PcQ ajg ef Qhi Yf GdfHi U ef GdUMGHI QVhGf Gddg Ydjges
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B254 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B17 - (3U (B16s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe LRA (B2/ 1 - (3U (B15 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3eUWdM (B254) s
Keywords: (3GdJGQjNs